About the borders of the Republic of Azerbaijan in the light of international recognized and adopted by the parties to the Gharabagh conflict of documents - Manasyan, Alexander (Bulletin of Yerevan University C: Jurisprudence, 2021)
The state border is one of the main the results of the realization of the people's right to self-determination, formalized in treaties with neighboring countries. In the 20th century, none of the three entities with the name Azerbaijan took place as an act of self-determination (referendum on independence). The first of them - the Azerbaijan Democratic Republic (ADR) - was established by the Turkish army invading Baku in September 1918. The League of Nations refused ADR membership for absurd land claims. ADR  left the history without established borders after the entry in April 1920 of the XI Red Army of Soviet Russia in Baku and the proclamation of the Azerbaijan Soviet Socialist Republic (AzSSR) as a non-national, without the titular nation of a republic of a new type, in which the Armenians were considered as one of its co-founders. By the declaration of December 2. 1920 the AzSSR recognized Nakhichevan and Zangezur as integral parts of the Armenian Soviet Socialist Republic (ArmSSR) and the right of the Nagorno-Karabakh (NK) people to complete self-determination. NK was declared an integral part of the Armenian SSR on June 12. 1921. Bolsheviks who colluded with the Kemalists in 1921 forcibly seized Nakhichevan and NK from the Armenian SSR in favor of the AzSSR. The borders of the AzSSR, which arose by these acts of annexation, could not be legitimate. Legally null and void were both the Treaty of Kars that is still in force, according to which Nakhichevan was given under the auspices of the AzSSR, and the decision of the Caucasian Bureau of the Russian Communist Party of Bolsheviks (Caucasian Bureau of the RCP (b)), which was not actually accepted (not even put to a vote). NK was torn away from the Armenian SSR with the condition of granting it "broad regional autonomy", but in violation of this condition in 1923 autonomy was decreed on one third of NK. The districts of NK bordering on the Armenian SSR remained outside the region. 1988-1991 Baku, in response to a request for reunification with the Armenian SSR, carried out genocidal acts against Armenians practically throughout the republic. On August 30, 1991, at the end of the collapse of the USSR, it was decided in Baku to abandon the succession of the AzSSR and restore the statehood of the ADR, which left without acquired borders and did not have sovereignty in NK. The Nagorno-Karabakh Republic (NKR) was proclaimed on September 2 on the territories not legally belonging to the AR. The political decision of the EU, adopted in December 1991, to recognize AR within the borders of the AzSSR did not give legitimacy to these borders, since they were formed as a result of annexations. The AR of our days has no legitimate borders. Its borders with the Republic of Armenia are now being "specified" for those territories seized from the Armenian SSR in 1921, which were supposed to be within the Autonomous Region of Nagorno-Karabakh. The article gives a legal assessment of the above and related to the topic of other documents.
Keywords: legitimacy of borders; Azerbaijan Democratic Republic; Azerbaijan Soviet Socialist Republic; Azerbaijan Republic; territorial integrity; genocidal behavior; state border; referendum on independence